2019
DOI: 10.1002/chem.201806116
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dipnictyl Analogues of Acrylamides, R−E=E′−CONR2, and a Related Diphosphadigalletane from Na[OCP] and (R2N)2ECl (E, E′=P, As, Ga)

Abstract: The reaction of Na[OCP] with (R2N)2ECl (E=P or As; R=alkyl) granted direct access to transient amine‐substituted diphospha‐ and arsaphospha‐acrylamide analogues, (R2N)E=P(CONR2) 1. Their facile formation allowed for a comprehensive reactivity study. Dimerization yielded the four‐membered rings (R2N)2E2P2(CONR2)2, whereas in the presence of excess Na[OCP], a stepwise [2+2] cycloaddition occured, leading to the sodium salts of carboxotripnictides [(R2N)EP2CO(CONR2)]−. These salts served as a reservoir of 1, eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…In compound 4 Ph The Bi−P distance is 262.40(7) pm and fits well to the bond lengths in 1 Ph (261.86(6) and 266.26(8) pm) and the other previously mentioned reference compounds [1,3,10,13,20,21] . The As−P bond has a length of 235.40(7) pm, which is in the usual range for covalent As−P single bonds [4,5,29–31] . The Bi−P−As angle around the central phosphorus atom is 113.58(3)°, much larger than the angle around the central P atom in compound 1 Ph (90.05(3))°.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In compound 4 Ph The Bi−P distance is 262.40(7) pm and fits well to the bond lengths in 1 Ph (261.86(6) and 266.26(8) pm) and the other previously mentioned reference compounds [1,3,10,13,20,21] . The As−P bond has a length of 235.40(7) pm, which is in the usual range for covalent As−P single bonds [4,5,29–31] . The Bi−P−As angle around the central phosphorus atom is 113.58(3)°, much larger than the angle around the central P atom in compound 1 Ph (90.05(3))°.…”
Section: Resultssupporting
confidence: 78%
“…[ 1 , 3 , 10 , 13 , 20 , 21 ] The As−P bond has a length of 235.40(7) pm, which is in the usual range for covalent As−P single bonds. [ 4 , 5 , 29 , 30 , 31 ] The Bi−P−As angle around the central phosphorus atom is 113.58(3)°, much larger than the angle around the central P atom in compound 1 Ph (90.05(3))°.…”
Section: Resultsmentioning
confidence: 91%
“…26 Gruẗzmacher and co-workers reported on species D (Scheme 1), which was accessed by the reaction of Na [OCP] with the secondary chloroarsane (iPr 2 )N 2 AsCl and further conversion of the intermediate species with dimethylbutadiene. 27 However, the reactivity of compounds containing single bonds between unlike pnictogen atoms is by far less investigated than the reactivity of the homonuclear derivatives. Goicoechea et al recently reported on the synthesis and reactivity of the (arsino)phosphaketene As(PCO){[N(Dipp)]-(CH 2 )} 2 (Scheme 1, B), which shows an interesting reactivity toward B(C 6 F 5 ) 3 , resulting in the formation of a cyclic cisarsaphosphene.…”
Section: ■ Introductionmentioning
confidence: 72%
“…Indeed, the P-and Ge-centred electrophiles led to the clean formation of the phosphaketene isomers RÀ P=C=O (similar to the C-electrophiles, see above). [56,[120][121][122] As for R: Me 2 Al, the phosphaalkyne (RÀ OÀ C�P) isomer was accessed using diisobutylaluminum chloride, [123] and our calculations predict only negligible difference between the stabilities of the two isomers. The ΔΔG 0 values for R: Me 3 Si or Me 2 B groups are also close to zero, indicating very similar stabilities of the two possible isomers.…”
Section: Chemistry-a European Journalmentioning
confidence: 89%